Pemberdayaan Masyarakat Melalui Program SERASI (Senam Raga Sehat, Cegah Hipertensi) untuk Meningkatkan Pengetahuan Hipertensi dan Aktivitas Fisik di Kampung Peundeuy, Kelurahan Ciakar, Kota Tasikmalaya - Fauziah, Ghaida; Yustika, Melti; Ramadani, Suci Indah; Mutiara, Euis Mira; Dewi, Suci Insani; Nafila, Lintana Muthi; Muhhary, Andy (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Hypertension is a non-communicable disease with a high prevalence in Indonesia, including in Tasikmalaya City, and shows a trend of increasing cases from year to year. This condition requires planned promotive and preventive efforts that involve community participation. This study aims to increase public knowledge about hypertension and the importance of physical activity as a preventive measure through the SERASI (Senam Raga Sehat, Cegah Hypertensi) program. The methods used include community-based health education, blood pressure checks, pre- and post-tests to measure changes in knowledge, and structured healthy exercise activities. The results showed a significant increase in knowledge after the intervention, reflected in the difference in pre- and post-test scores with a p value of 0.000 (p < 0.05). In addition, healthy exercise activities increased community participation and involvement, and encouraged the formation of sustainable physical activity habits. Overall, the SERASI program has proven effective in increasing community knowledge, awareness, and behavioral changes towards hypertension prevention, thus potentially supporting risk factor control and improving the quality of local community health. These findings are relevant for planning sustainable local and national community-based public health programs.